Legal Analysis of The Criminal Act of Murder Against a Child by The Biological Parents Which Was Planned from a Criminological Perspective: (Study of Decision Number 4/Pid.B/2024/Pn MSH) - (Firda), Firdaus; Suartini, Suartini (PT Mattawang Mediatama Solution, 2024)
This research analyzes the crime of premeditated murder of children by biological parents from a criminological perspective, focusing on Decision No. 4/Pid.B/2024/PN Msh. The aim of this research is to examine the considerations of judges in relation to the premeditated murder of children by parents, as well as to understand the psychological, social and economic factors that encourage such actions. The method used is juridical-normative, analyzing relevant laws and regulations such as the Penal Code and the Child Protection Act. Data was collected from legal literature, regulations and court decisions. The results showed that social pressure, community stigma and mental health problems were the main factors behind this crime. The court used Article 342 of the Penal Code to sentence the mother to 1 year and 10 months imprisonment. In conclusion, the judge's consideration was in line with the applicable legal framework, emphasizing the deterrent effect and the rehabilitation of the offender.